Wrist Circumference-Dependent Upper Limit of Normal for the Cross-Sectional Area Is Superior Over a Fixed Cut-Off Value in Confirming the Clinical Diagnosis of Carpal Tunnel Syndrome - Olde Dubbelink, Tom B. G.; De Kleermaeker, Floriaan G. C. M.; Beekman, Roy; Wijntjes, Juerd; Bartels, Ronald H. M. A.; Meulstee, Jan; Verhagen, Wim I. M. (Frontiers in Neurology, 2021)
Introduction: In confirming the clinical diagnosis of carpal tunnel syndrome (CTS), ultrasonography (US) is the recommended first diagnostic test in The Netherlands. One of the most important parameters for an abnormal US result is an increase of the CSA of the median nerve at the carpal tunnel inlet. An earlier study showed that a wrist-circumference dependent cut-off for the upper limit of normal of this CSA might be superior to a fixed cut-off of 11 mm2. In this study we compared three ultrasonography (US) parameters in three large Dutch hospitals. Methods: Patients with a clinical suspicion of CTS and with reasonable exclusion of other causes of their symptoms were prospectively included. A total number of 175 patients were analysed. The primary goal was to compare the number of wrists with an abnormal US result while using a fixed cut-off of 11 mm2 (FC), a wrist circumference-dependent cut-off (y = 0.88 * x−4, where y = ULN and x = wrist circumference in centimetres; abbreviated as WDC), and an intraneural flow related cut-off (IFC). Results: The WDC considered more US examinations to be abnormal (55.4%) than the FC (50.3%) did, as well as the IFC (46.9%), with a statistically significant difference of p = 0.035 and p = 0.001, respectively. The WDC detected 12 abnormal median nerves while the FC did not, and 18 while the IFC did not. The wrist circumference of the patients of these subgroups turned out to be significantly smaller (p < 0.001) when compared with the rest of the group. Conclusion: According to these study results, the wrist-circumference dependent cut-off value for the CSA of the median nerve at the wrist appears to have a higher sensitivity than either a fixed cut-off value of 11 mm2 or cut-off values based on intraneural flow, and may add most value in patients with a smaller wrist circumference.